2003
DOI: 10.14488/1676-1901.v3i1.607
|View full text |Cite
|
Sign up to set email alerts
|

<b>Projeto de minimização de resíduos sólidos no restaurante central do campus de São Carlos da Universidade de São Paulo</b>

Abstract: This paper presents the project for the minimisation of the solid residues which are produced by the Central Restaurant of the São Carlos Campus of the University of São Paulo which was carried out by a partnership involving the USP Recicla Programme and the Department of Production Engineering. The basis of this programme is the 3 R's principle: Reducing, Reusing and Recycling. There was also a great concern with the involvement of the users' community of this restaurant. The cost reduction originated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…The second mechanism is the Rayleigh scattering by molecules. Using AO-assisted IFU spectroscopy in the K band, we have detected a weak molecular emission of H 2 in the nuclear region of M104 (Menezes 2012;R. B. Menezes & J. E. Steiner 2013, in preparation).…”
Section: Discussionmentioning
confidence: 95%
“…The second mechanism is the Rayleigh scattering by molecules. Using AO-assisted IFU spectroscopy in the K band, we have detected a weak molecular emission of H 2 in the nuclear region of M104 (Menezes 2012;R. B. Menezes & J. E. Steiner 2013, in preparation).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a slight bias level difference between these amplifiers could be an explanation for this fingerprint. We used the Principal Component Analysis Tomography technique (Steiner et al 2009) to remove the fingerprint from the data cube of M104, following the prescription of Menezes et al (2014Menezes et al ( , 2015.…”
Section: Observations Reduction and Data Treatmentmentioning
confidence: 99%
“…A comparison with an I -band image of M104 obtained with the Widefield Planetary Camera 2 (WFPC2) of the HST revealed that the FWHM of the PSF of the data cube was ∼ 0 ′′ .3, before the Richardson-Lucy deconvolution, and ∼ 0 ′′ .15, after the Richardson-Lucy deconvolution. For more details about the data treatment procedure we performed, see Menezes et al (2014Menezes et al ( , 2015. An image of the treated data cube of M104 collapsed along the spectral axis, together with its average spectrum, is shown in Figure 1.…”
Section: Observations Reduction and Data Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre as ações de reduzir os resíduos inorgânicos gerados em uma UAN, Carneiro et al (2010) propõe que as empresas devem dar preferência para produtos de higiene que tenham refil e pela utilização de copos de vidro ao invés de copos de plástico. Menezes (2002) com a finalidade de reduzir resíduos recicláveis oriundos de copos plásticos não conseguiu implantar a utilização de copos de vidro, mas conseguiu uma redução de 50% do descarte pela conscientização dos usuários em evitar o consumo excessivo de copos após um trabalho educativo desenvolvido na UAN. b) Reduzir a geração de resíduos orgânicos no estoque pelo controle de mercadoria no estoque.…”
Section: Reduzirunclassified